Advanced metal oxide (supported) catalysts: Synthesis and applications - Lee, Dong Won; Yoo, Bok Ryul (ELSEVIER SCIENCE INC, 2014)
A variety of metal oxides catalysts are used in heterogeneous catalysis for chemical processes and have now been developed for their catalytic performance and durability. The heterogeneous catalysis is the most important technology in chemical industry as well as other environmental, energy applications, etc. This review examines recent advances at the preparation and applications of metal oxide particles, especially pertaining to catalytic enhancements for current and future chemical process such as Fischer-Tropsch process, alkylation, and transesterification and environmental applications such as the oxidation of volatile organic compounds and the reduction of NOx. (C) 2014 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: FISCHER-TROPSCH SYNTHESIS; VOLATILE ORGANIC-COMPOUNDS; SURFACE-REACTION RATES; CO-MN CATALYST; PARTIAL OXIDATION; BIODIESEL PRODUCTION; CARBON-MONOXIDE; FIXED-BED; VEGETABLE-OILS; SPECTROSCOPIC CHARACTERIZATION